Escaping the Density Trap: Estuarine Connectivity Supports Juvenile River Herring Growth - Julian D. Burgoff; Allison H. Roy; Douglas Bishop; Jason Stolarski; Adrian Jordaan (Estuaries and Coasts, 2026)
Alewife ( Alosa pseudoharengus ) and blueback herring ( A. aestivalis ) require connectivity among freshwater, estuarine, and marine environments to complete their life cycle. Impediments to watershed connectivity are major drivers of population declines along the eastern United States, where physical barriers and low-flow conditions can inhibit or delay juvenile outmigration, limiting access to productive estuarine nursery habitats. Because juvenile growth strongly influences early survival and recruitment, understanding how connectivity to estuaries shapes growth across nursery habitats is critical but remains poorly understood. We evaluated juvenile river herring growth across connected lake, river, and estuary habitats in three coastal Massachusetts watersheds from 2021 to 2023. Juvenile fish and water quality were sampled throughout each summer, and sagittal otoliths were used to estimate growth rates. Juvenile growth was enhanced in downstream estuarine habitats where connectivity was intact and in-lake juvenile densities were high, as observed in the Weymouth Back River watershed. In contrast, growth limitations occurred in a high-density system with restricted passage, where juveniles occupied shallow, eutrophic river reaches in the Mystic River watershed. Growth rates were similar between lake and estuarine habitats in a low-density system (Essex River watershed), indicating that estuarine benefits to growth are context dependent. Together, these results demonstrate that connectivity to estuarine habitats can alleviate density-dependent growth constraints, but that barriers and delayed outmigration to estuaries can limit these benefits. Maintaining or restoring functional freshwater–estuarine connectivity is therefore critical for sustaining juvenile production and provides a clear management priority for municipalities, state and federal agencies, and watershed managers working to restore river herring populations in fragmented coastal systems.